Influencia de la prematuridad en los aspectos nutricionales, metabólicos e inflamatorios de los niños en edad preescolar.: Influência da prematuridade nos aspectos nutricionais, metabólicos e inflamatórios de pré-escolares. - Simone Raposo Miranda; Melo, Camila Yandara Sousa Vieira de Melo; Vieira, Nathalia Fidelis Lins Vieira; Santos, Ana Célia Oliveira (Nutrición Clínica y Dietética Hospitalaria, 2023)
Objective: To identify an association between prematurity and the nutritional, metabolic and inflammatory aspects of pre-school children. Methods: This was a case-control study with 32 preterm children and 32 full-term children. A nutritional diagnosis was obtained through the anthropometric indexes of height/age (H/A) and BMI/Age (BMI/A) using the WHO AnthroPlus® program. Metabolic assessment was performed through the levels of fasting glucose, fasting insulin, total cholesterol, triacylglycerides, high-density lipoprotein and low-density lipoprotein. The inflammatory profile was identified through the serum levels of interleukin 6 (IL-6) and C-reactive protein (CRP). Results: The assessment age of preterm children was 81 months ± 23.8. A shorter gestation time was associated with an increased waist circumference (p=0.035), and total cholesterol levels (p=0.031), and tended toward an association with higher interleukin 6 levels (p=0.062). Waist circumference was associated with higher adiposity (p=0.003) and with increased blood pressure (p=0.010). Conclusion: Preterm birth was related to increased levels of total serum cholesterol and increased waist circumference, thereby suggesting a higher risk of future cardiovascular events. No association was observed between gestational age and birth weight with other nutritional, metabolic or inflammatory aspects in the pre-school children assessed.